“What makes this a wug?” Relations among children’s question asking, memory, and categorization of objects - Lazaroff, Emma; Vlach, Haley A. (Frontiers in Psychology, 2022)
Children ask many questions, but don’t always receive answers to the questions they ask. We were interested in whether the act of generating questions, in the absence of an answer, is related to children’s later thinking. Two experiments examined whether children retain the questions they ask in working memory, and whether the type of questions asked relate to their categorization. Four to ten-year-old children (N = 42 in Experiment 1, N = 41 in Experiment 2) were shown 12 novel objects and asked three questions about each and did not receive answers to their questions. Children recalled their questions in the first experiment and categorized variants of the novel objects in the second experiment. We found that children have robust working memory for their questions, indicating that these questions may relate to their subsequent thinking. Additionally, children generalize category boundaries more narrowly or broadly depending on the type of question they ask, indicating that children’s questions may reflect an underlying bias in how they think about the world. These findings suggest that future research should examine questions in the absence of answers to understand how inquiry affects children’s cognitive development.